Aerosonde Simulation - Pelham, Joni (Cranfield University, 2018)
Aerosonde Simulink simulation with mission simulator, and fault simulator. Development of work by Whidborne, Saban, et al
Keywords: Matlab/Simulink'; 'flight simulation ,'; 'Autonomous Vehicles'